Bibliometric Analysis in Studies on Good Corporate Governance and Financial Performance - Judijanto, Loso (Westscience Press, 2025)
This study conducts a bibliometric analysis of research on Good Corporate Governance (GCG) and financial performance using data from Scopus and analyzed through VOSviewer. The analysis identifies key research trends, influential authors, collaboration networks, and thematic clusters within the field. Findings indicate that agency theory remains the dominant theoretical framework, while stakeholder and stewardship theories are gaining prominence. The study highlights the strong relationship between corporate governance mechanisms, such as board structure, ownership concentration, and audit committees, and financial performance indicators like return on assets (ROA) and Tobin’s Q. Additionally, emerging themes such as corporate strategy, intellectual capital, and sustainability are shaping the evolving governance landscape. Geographic analysis reveals that Indonesia, Malaysia, and Nigeria are emerging research hubs, while Western countries maintain significant influence in governance literature. The study underscores the need for cross-regional collaboration, advanced analytical methodologies, and integration of ESG factors into governance frameworks. These insights provide valuable contributions to both academic discourse and policy development, emphasizing the role of governance in driving corporate financial success.